Implementasi Reformasi Birokrasi Menuju Tata Kelola Pemerintahan Yang Baik: (Studi kasus: Pemerintah Kabupaten Kulon Progo) - Alim Muhammad Dwijaya; Ristanto Ristanto; Tri Hidayat; Mega Wati; Monika Monika (CV. ULIL ALBAB CORP, 2024)
Bureaucratic reform requires changes in mindset, work patterns and performance of every state apparatus. However, often the implementation is still far from what is expected from the objectives of implementing bureaucratic reform. The aim of this research is to determine the extent to which bureaucratic reform has been implemented in order to realize good governance in the Kulon Progo Regency Government. This research uses a qualitative methodology by prioritizing interviews and documentation. As for the research results, it can be concluded that the implementation of Kulon Progo district bureaucratic reform has gone well with the achievement of a